Источники Cl-, Br- и I-содержащих атмосферных примесей в составе ледника о. Галиндез, ст. Вернадский - Богилло, В.И.; Борхерс, Р.; Базилевская, М.С. (Український антарктичний журнал, 2005)
В работе рассмотрены возможные источники летучих Cl, Br- и I-содержащих галогенуглеводородов и предложены механизмы их образования из этих источников, обнаруженных в больших концентрациях в слоях молодого и древнего льда деградирующего ледника о. Галиндез, архипелаг Аргентинские острова, Западная прибрежная Антарктида. Их атмосферные соотношения смеси в этих образцах сравнимы с результатами анализа воздуха в глубоких кернах фирна из Центральной Антарктиды, Центральной Гренландии и Канадской Арктики и с содержанием этих галогенуглеводородов в атмосфере над Южным океаном. Показано, что CH₂Br₂ и CHBr₃ могут образовываться из ледяных микроводорослей на поверхности снега ледника и из прибрежных макроводорослей, занесенных ветром на эту поверхность по механизмам галоформной реакции и/или галогенсульфонового перегруппирования. Для найденных с высокой концентрацией в образцах льда моногалогенуглеводородов (CH₃Cl, C₂H₅Cl, CH₂=CHCl, CH₃Br, CH₃I, CH₂=CHI и C₂H₅I) возможны аналогичные источники. Кроме того, они могут образовываться в результате таких абиотичных реакций, как фотолизорганического вещества, которое образовалось при гибели водорослей на поверхности снега, в присутствии ионов галогена по механизму реакции Норриша I-типа (фотодиссоциация α-карбонила) окислительно-восстановительной реакции этого вещества с ионами Fe³⁺ и ионами галогена в более глубоких слоях снега и фирна ледника. Приведены возможные концентрации указанных ионов и соединений в антарктическом снегу и проведено сравнение скоростей этих абиотических процессов. В даній роботі розглянуті можливі джерела та запропоновані механізми утворення летких Cl, Br- та I-містких галогенвуглеводнів з цих джерел, знайдених у високих концентраціях у шарах молодого та давнього льоду деградуючого льодовика о. Галіндез, архіпелаг Аргентинські острови, Західна прибережна Антарктида. Їх атмосферні співвідношення суміші в цих зразках льоду близькі до результатів аналізу повітря в глибоких кернах фірну з Центральної Антарктиди, Центральної Гренландії та Канадської Арктики і до вмісту цих галогенвуглеводнів в атмосфері над Південним океаном. Показано, що CH₂Br₂ та CHBr₃ можуть утворюватися з льодових мікроводоростей на поверхні снігу льодовика і з прибережних макроводоростей, занесених вітром на цю поверхню за механізмами галоформної реакції та/чи галогенсульфонового перегрупування. Для знайдених у високих концентраціях у зразках льоду моногалогенвуглеводнів (CH₃Cl, C₂H₅Cl, CH₂=CHCl, CH₃Br, CH₃I, CH₂=CHI та C₂H₅I) можливі аналогічні джерела. Крім того, вони можуть утворюватися в результаті таких абіотичних реакцій, як фотоліз органічної речовини, яка створилася при загибелі водоростей на поверхні снігу, в присутності іонів галогену за механізмом реакції Норіша I-го типу (фотодисоціація α-карбонілу) та окисно-відновної реакції цієї речовини з іонами Fe³⁺ та іонами галогену в більш глибоких шарах снігу та фірну льодовика. Наведені можливі концентрації вказаних іонів та сполук в антарктичному снігу та проведено порівняння швидкостей цих абіотичних процесів. The volatile halocarbons play a key role in depletion of stratospheric ozone layer, in change of oxidative potential of troposphere and in atmospheric radiation balance. However, the relative contributions of their fluxes from anthropogenic and such natural sources, as lithosphere, soils, terrestrial plants, oceanic biota, biomass burning, abiotic photo- and redox-reactions of natural organic matter in presence of halide ions are not known enough. The possible sources have been discussed for volatile Cl, Br- and I-containing halocarbons identified in high concentrations in young and aged layers of retreated glacier on Galindez Island, Argentinean Islands Archipelago, Western coastal Antarctica and the formation mechanisms have been proposed here. Their atmospheric mixing ratio in the ice samples has been compared with the results for air analysis in deep cores of firn from Central Antarctica, Central Greenland and Canadian Arctic, and with their content in air over Southern Ocean and in the water. It was shown that CH₂Br₂ and CHBr₃ can be formed from ice microalgaes deposited on the snow surface and from coastal macroalgaes wind-blown on the surface through the mechanism of haloform reaction and/or sulfo- haloform rearrangement. Similar sources are possible for mono-halocarbons (CH₃Cl, C₂H₅Cl, CH₂=CHCl, CH₃Br, CH₃I, CH₂=CHI and C₂H₅I), which found in high concentrations in the ice samples. The alkylation of the halide ions by sulphur-containing bioorganic compounds or reaction of chloroperoxidase with organic compounds containing CH group activated by carbonyl group in presence of hydrogen peroxide and halide ions can be main mechanisms for biogenic formation of the halocarbons. Furthermore, they may be formed in consequence of such abiotic reactions as photolysis of organic matter generated from the deceased algaes on the snow surface in presence of halide ions in accordance with mechanism of Norrish II type reaction (photodissociation of α-carbonyls) and/or oxidation-reduction reaction of the matter with F³⁺ ions and halide ions in more deep layers of snow and firn of the glacier. The possible concentrations of the ions and the compounds in Antarctic snow were obtained and the rates of these processes were compared. It was found that photolysis of the organic matter is more effective in comparison with the redox-reaction of the matter. The temporal variations of CH₃Cl, C₂H₅Cl, CH₃Br, CH₃I and C₂H₅I along the glacier profile were analyzed and compared with those obtained for CO₂ and COS. It was found that hydrolysis processes of CH₃Br and CH₃I in quasi-liquid water films on the snow and firn surface as well as in the infiltrated water have a great impact on the temporal variations for these compounds whereas the effect of nucleophilic substitution reactions of Cl- ion in these species can be neglected.